(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
The male and female gonads play a fundamental role in human reproduction and endocrine regulation. This article examines the morphological and functional characteristics of the testes and ovaries, highlighting their structural organization and physiological roles. Special attention is given to gametogenesis, hormonal secretion, and the interaction between gonadal activity and the endocrine system. The study also explores the regulatory mechanisms controlled by the hypothalamic–pituitary–gonadal axis and their significance in maintaining reproductive health. Understanding the structural and functional features of gonads provides important insights into normal physiology as well as reproductive disorders.